Contemporary structuring of corporate waqf via Islamic real estate investment trusts (i-reits): is it viable? - Sulaiman, Syahnaz; Hasan, Aznan; Shafii, Zurina (USIM Press, 2019)
Waqf or Islamic endowment is an important institution in the social sector (ijtimia’i sector) of the Islamic economic system that has contributed significantly towards socio-economic and social development since the early days of Islam. There is an abundance of historical evidence that has shown the commendable contribution of waqf as a primary socio-economic vehicle for financing Muslim society (Hodgson, 1974) without incurring any cost to the government (Mohsin, 2010; Cizakca, 1998). A substantial amount of literature has discussed the great contributions of waqf, and the importance of effective and efficient management role of waqf institution in enhancing the socio-economic development.